Jd-hrm: a scenario-based approach - Noranee, Shereen; Ahmad, Nursaadatun Nisak; Adha Hafit, Nor Intan; Mustapa, Zuhaina (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project introduces an innovative teaching method that integrates theoretical knowledge with practical HRM applications through interactive, scenario-based modules. Focusing on job descriptions (JDs), recruitment, and selection, it addresses gaps in students' comprehension and skills while enhancing critical thinking, problem-solving, and workforce optimization. By bridging academic learning with real-world HR challenges, this approach fosters both confidence and competence in future HR professionals. JDs and job specifications are foundational to effective HR functions, particularly recruitment and selection. They provide clarity on roles, responsibilities, and qualifications, ensuring alignment between organizational needs and candidate profiles. Updated and relevant JDs are vital as they reflect current job demands and market trends, enabling HR processes like onboarding, training, and performance management to remain effective. Outdated documents, by contrast, risk inefficiencies and misalignments, negatively impacting employee satisfaction and productivity. This method’s socio-economic impact includes preparing a skilled workforce aligned with organizational goals, improving hiring quality, reducing turnover, and enhancing organizational efficiency. With its adaptability to diverse HR contexts and strong potential for scalability, this innovation offers promising commercialization opportunities in academic and corporate training environments, driving sustainable workforce development and economic productivity.